PERAN ANGGOTA LEGISLATIF PEREMPUAN DI KABUPATEN BANJARNEGARA DALAM PROSES PENGAMBILAN KEPUTUSAN POLITIK MASA SIDANG 2019-2020 - Dinda Meisy Puspitasari; Muhammad - Adnan (Journal of Politic and Government Studies, 2021)
Women legislative members are individuals who have social status in society to achieve certain goals in decision-making process to resolve existing problems by exercising their rights and obligations according to their position and role as representatives of the people. In this thesis, authors took the title The Role of Women Legislative Members in Banjarnegara Regency in the Political Decision Making Process for the 2019-2020 Session Period. A woman legislative member will complement the world of politics in Banjarnegara Regency with all her feminine traits, because  women usually will be more sensitive to political issues related to women, such as maternal and child health, domestic violence, and so on, they can donating strategic ideas and thoughts in improving the fate of the people and being able to accommodate needs of women in Banjarnegara Regency through the process of making political decisions. The problem in this thesis is what is the role of women legislative members in Banjarnegara Regency in the process of making political decisions during the2019-2020?. This thesis used descriptive-qualitative method, the type of data are interviews, documents, observations, and several relevant sources such as journals and in the form of theories related to this thesis. The research location is in DPRD Banjarnegara Regency. The informants in this thesis are 13 women legislative members; Head of the Banjarnegara Regency DPRD, and Head of the Department of Women's Empowerment and Child Protection. In the 2019-2024 period, most of the women legislators held strategic positions, such as Chair of the Commission, Deputy of the Commission, Chair of the Faction, Secretary of the Faction, Chair and Deputy Chair of the DPRD Organizing Committee. The results obtained in this thesis indicate that the role of women legislative members in Banjarnegara Regency in the 2019-2020 period is quite good, as evidenced by their existence in every activity and organization both in the office and outside the office. This is supported by the achievements of women legislative members in making decisions to deal with problems in Banjarnegara Regency, such as achieving the elimination of student worksheets for school children, currently discussing Child-Friendly District Regulations, although they have not yet achieved 100% success but are good enough in their implementation and in carrying out the functions of legislation, budget and supervision.